2023
DOI: 10.1186/s12865-023-00540-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimized workflow to modify microRNA expression in primary human intravascular cells

Abstract: Background A comprehensive dissection of the role of microRNAs (miRNAs) in gene regulation and subsequent cell functions requires a specific and efficient knockdown or overexpression of the miRNA of interest; these are achieved by transfecting the cell of interest with a miRNA inhibitor or a miRNA mimic, respectively. Inhibitors and mimics of miRNAs with a unique chemistry and/or structural modifications are available commercially and require different transfection conditions. Here, we aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The important role of lipofectamine as a nanocarrier to enable encapsulation of nucleic acids into cells [ 19 ] and to enhance the delivery of nanoparticles into cells was described before [ 20 ]. Caglayan et al found that elevated concentrations of mirVana or locked nucleic acid miR-15a-5p mimic that were delivered to endothelial cells using lipofectamine RNAiMAX as a carrier specifically increased the expression of miR-15a-5p [ 41 ]. Magro et al revealed that nanomaterials can be successfully internalized into mesenchymal stem cells transfected with lipofectamine by an increase in GFP expression [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The important role of lipofectamine as a nanocarrier to enable encapsulation of nucleic acids into cells [ 19 ] and to enhance the delivery of nanoparticles into cells was described before [ 20 ]. Caglayan et al found that elevated concentrations of mirVana or locked nucleic acid miR-15a-5p mimic that were delivered to endothelial cells using lipofectamine RNAiMAX as a carrier specifically increased the expression of miR-15a-5p [ 41 ]. Magro et al revealed that nanomaterials can be successfully internalized into mesenchymal stem cells transfected with lipofectamine by an increase in GFP expression [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in a cancer-dependent context, lncRNAs may be overexpressed to either inhibit or decrease the level of PTEN targeting microRNAs, thereby increasing PTEN expression and activity as a tumour suppressor. Furthermore, miRNAs can be depleted using miRNA inhibitors, or 'sponges' [177], in order to increase PTEN or PTENP1 levels in cells.…”
Section: Altering Levels Of Mirnas Targeting Pten and Ptenp1mentioning
confidence: 99%
“…Estrogen plays an essential role in the occurrence of endometrioid carcinoma and affects the negative feedback loop of PTEN-miR-200c-PTENP1 [114]. Thus, the upregulation of certain miRNAs using miRNA mimics [177] could be a useful potential cancer therapy depending on the cancer type.…”
Section: Altering Levels Of Mirnas Targeting Pten and Ptenp1mentioning
confidence: 99%
See 1 more Smart Citation